Pengaruh Motivasi dan Fasilitas Belajar terhadap Hasil Belajar Bahasa Inggris Siswa SMP Alang Alang Lebar - Sri Hestysetyaningsih; Bukman Lian; Setiyo Nugroho (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of learning motivation and learning facilities on the English learning outcomes of junior high school students in the Alang Alang Lebar District, Palembang City. The background of the research highlights the importance of English proficiency as a 21st-century skill that requires both internal and external support factors. Learning motivation, which includes intrinsic and extrinsic drives, is believed to increase students’ interest and active participation in the learning process. Meanwhile, learning facilities such as adequate classrooms, audio-visual equipment, and access to digital learning media serve as significant supporting factors. This research employs a quantitative approach with a survey method. Data were collected through questionnaires distributed to students from several junior high schools in the Alang Alang Lebar area. Data analysis was conducted using multiple linear regression to examine the effect of each independent variable on English learning outcomes. The findings reveal that learning motivation has a positive and significant effect on English achievement. Learning facilities also contribute substantially to improving students’ academic performance. Furthermore, the combination of high motivation and adequate facilities leads to greater improvements in English scores. These results emphasize that successful learning depends not only on teachers’ instructional methods but also on motivational support and sufficient resources. The study recommends that schools and policymakers enhance programs that foster motivation and upgrade learning facilities as strategic efforts to improve the quality of students’ English learning outcomes.